Análisis y simulación de los protocolos de enrutamiento OSPFV3 y EIGRP para IPV6 para la empresa LIMPIOMAR del cantón Babahoyo. - Sagñay Castillo, Darla Duvanna (2022)
The great growth in the use of networks arises from the inconvenience of the depletion of address space of the IPv4 Internet Network Protocol, which prevents satisfying all the services requested by users. For which the development of the new Network Protocol called IPv6 arises. The IPV4 protocol was very well implemented and until now it is the most widely used in communication networks. The great problem of both protocols is their incompatibility, which is why the Dual Stack transition mechanism was born. This case study includes a comparative analysis between the different OSPFV3 and EIGRP Protocols for IPv6, LIMPIOMAR company located in Babahoyo canton in order to determine which of the two, the impact is caused during the transition process to IPv6. The qualitative methodology will be used for the collection of information, an interview will be used, which through a questionnaire of open questions will consider finding relevant information for the company. The next generation Internet Protocol will be IPv6, which provides a large address space and a simple header format. By describing the main features, advantages, and disadvantages of the OSPFV3 and EIGRP routing protocols for IPV6, it was possible to gain a clearer idea of the benefits they could provide. With the comparative analysis between the routing protocols OSPFV3 and EIGRP for IPV6, it is concluded that the routing protocol that causes the least impact at the time of transition from IPV4 to IPV6 is EIGRP version 6 for IPV6. With the IPV6 network protocol, the internet network will be faster, more secure and reliable, to be able to access services in real time. You need to choose one of the routing protocols in conjunction with the Dual Stack transition method.